Cross – Cultural Pragmatic Failure - NOUICHI, Fahima (Journal of Human Sciences, 2014)
Successful communication in a second language needs both, the linguistic and the pragmatic competences of that language. But the common mistake second language learners make is that they rely more on linguistic knowledge rather than communication. As a result, they become linguistically competent but pragmatically incompetent, and still make mistakes in their communication with native speakers. These mistakes lead to “cross-cultural pragmatic failure”. Hence, this paper will deal with the problem of “cross-cultural pragmatic failure”. It aims at highlighting the importance of improving the pragmatic and communicative competence of second language learners through analyzing the sources of pragmatic failure and developing the awareness of cross-cultural pragmatics.